1991
DOI: 10.7748/ns.5.23.25.s46
|View full text |Cite
|
Sign up to set email alerts
|

Complementary therapy in practice

Abstract: Dorothy Crowther describes the evolution of the Wirral Holistic Care Services, a company dedicated to helping people cope with cancer. Based on a recognition that such patients want more than the standard NHS fare, initial evaluations suggest that the company is going some way to meeting the extra needs of this group. Available therapies include aromatherapy, kinesiology, reflexology and meditation, incorporating a model of care which endorses putting the patient first.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A midwife (Tiran, 1996) used reflexology to treat a mother's stiff neck and headache from an epidural reaction following delivery; the patient did not require a blood-patch procedure. Crowther (1991) noted that Wirral Holistic Care services, a center established to offer British cancer patients complementary therapies, offered reflexology. In Switzerland, Dobbs (1985) reported that reflexology provided pain relief in seven hospitalized patients with terminal cancer; as a side effect, patient and family morale increased.…”
Section: Origin Of and Cases Using Reflexologymentioning
confidence: 99%
“…A midwife (Tiran, 1996) used reflexology to treat a mother's stiff neck and headache from an epidural reaction following delivery; the patient did not require a blood-patch procedure. Crowther (1991) noted that Wirral Holistic Care services, a center established to offer British cancer patients complementary therapies, offered reflexology. In Switzerland, Dobbs (1985) reported that reflexology provided pain relief in seven hospitalized patients with terminal cancer; as a side effect, patient and family morale increased.…”
Section: Origin Of and Cases Using Reflexologymentioning
confidence: 99%
“…Although many studies of refl exology have been conducted on various conditions since the 1980s (Ashkenazi, 1993;Crowther, 1991;Dobbs, 1985;Frankel, 1997;Hang, 1991;Liang, 1996;Marquardt, 2000;Tiran, 1996), only recently have small pilot studies looked at refl exology's use for pain reduction in patients with cancer in the hospital. Stephenson, Weinrich, and Tavakoli (2000) conducted a study in an inpatient setting and found a signifi cant decrease in pain among patients with breast cancer following foot refl exology (n = 11, p = 0.048).…”
mentioning
confidence: 99%
“…The nurse can then begin to use various techques such as massage and therapeutic touch. Crowther [ 1991 ] believes that these so-called 'alternative' therapies can help the cancer patient to overcome many of the worst effects of their illness. Music in the background and a slow monotonous speech pattern can also be used to good effect by the nurse.…”
Section: Methods Of Pain Relief Available To the Nursementioning
confidence: 99%